Consumption patterns before and during the COVID-19 pandemic among patients admitted to inpatient drug detoxification treatment: Results of two cross-sectional surveys from 2018 and 2021 - Roser, Patrik; Specka, Michael; Bonnet, Udo; Kuhlmann, Thomas; Kühnhold, Stefan; Steinert, Renate; Zeiske, Benita; Deimel, Daniel; Scherbaum, Norbert (Frontiers in Psychiatry, 2024)
BackgroundThe lockdown measures during the SARS-CoV-2 pandemic could have influenced drug consumption patterns of persons with drug use disorder, especially due to a reduced availability of drugs, an increased consumption of sedating substances as a coping strategy, or a shift to novel psychotropic substances (NPS) associated with an increased drug buying in the internet. In this study, the consumption patterns of people mainly with opioid use disorder entering inpatient drug detoxification treatment were investigated in the same hospitals with the same methods before and during the pandemic.MethodsAt admission, patients were interviewed regarding their consumption patterns using the EuropASI questionnaire. In addition, changes in the routes of drug acquisition were assessed.ResultsIn five hospitals in Western Germany, 213 (2021) and 175 persons (2018) were recruited. Sociodemographic data were similar in both cohorts (mean age around 40 years, mainly male, about 50% with migrant background, high unemployment rate). Rates of use of various drugs during the last 30 days were also similar. Differences were detected for gabapentinoids and opioid analgesics (increase >5%) as well as for cannabis (decrease >5%). Current use of NPS was low in both surveys. Only a minority of patients had experiences with drug acquisition in the internet.DiscussionThe pandemic had only a minor influence on consumption patterns and routes of drug acquisition in this sample. It remains to be seen whether the increased use of gabapentinoids and opioid analgesics will continue despite the end of the pandemic.